2010
DOI: 10.2967/jnumed.109.073189
|View full text |Cite
|
Sign up to set email alerts
|

PET of Hypoxia with89Zr-Labeled cG250-F(ab′)2in Head and Neck Tumors

Abstract: Hypoxic tumor cells are resistant to radiotherapy and various chemotherapeutic agents. The pretherapeutic assessment of intratumoral hypoxia may allow selection of patients for intensified treatment regimens. Carbonic anhydrase IX (CAIX) is an endogenous hypoxia-related protein involved in pH regulation and is upregulated in many tumor types. Radionuclide imaging using a monoclonal antibody against CAIX, such as cG250, may allow noninvasive PET of hypoxia in these tumor types. The aims of this study were to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 34 publications
0
78
0
1
Order By: Relevance
“…This has, to our knowledge, never before been reported for CD44v6-binding radioimmunotargeting molecules. For other targets, enzymatically derived divalent F(ab') 2 and monovalent Fab' fragments have shown promising results in animal studies (24)(25)(26)(27)(28) and clinical studies (29,30) and F(ab') 2 fragments against a different target in HNSCC (E48) has been shown to be equally effective as the parent antibody, in tumor and lymph node detection with planar gamma camera (31).…”
Section: Discussionmentioning
confidence: 99%
“…This has, to our knowledge, never before been reported for CD44v6-binding radioimmunotargeting molecules. For other targets, enzymatically derived divalent F(ab') 2 and monovalent Fab' fragments have shown promising results in animal studies (24)(25)(26)(27)(28) and clinical studies (29,30) and F(ab') 2 fragments against a different target in HNSCC (E48) has been shown to be equally effective as the parent antibody, in tumor and lymph node detection with planar gamma camera (31).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, F(ab′) 2 fragments demonstrate high tumor-to-background signal ratios at earlier time points, while retaining tumor-binding characteristics similar to those of whole antibodies (11,12). Previous in vivo studies have shown that 111 In-cetuximab-F(ab′) 2 can visualize EGFR accessibility in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Cetuximab and cetuximab-F(ab9) 2 were conjugated to isothiocyanatobenzyl-diethylenetriaminepentaacetic acid (ITC-DTPA; Macrocyclics) in 0.1 M NaHCO 3 , pH 9.5, for 1 h at room temperature using a 50-fold molar excess of ITC-DTPA (14,15). Unbound ITC-DTPA was removed by dialysis against NH 4 OAc (0.25 M, pH 5.5).…”
Section: Radiolabeling and Quality Controlmentioning
confidence: 99%
“…Antibody F(ab9) 2 fragments of cetuximab IgG have a lower molecular weight and therefore display faster blood-/tissue-clearance kinetics and enable earlier high-contrast molecular imaging (15). In this study, we aimed to characterize and optimize cetuximab-F(ab9) 2 as an EGFR-targeting imaging agent in HNSCC.…”
mentioning
confidence: 99%